Import promotion as an instrument of development cooperation: Lessons from European experiences for Austrian development cooperation - Jan Grumiller; Werner G. Raza (Austrian Foundation for Development Research (ÖFSE), 2019)
This briefing paper discusses import promotion agencies (IPOs) as a comparatively new instrument of development cooperation in Europe. The paper assesses the potential of import promotion agencies to promote exports from Low Income Countries (LICs) to High Income Countries (HICs). The comparative analysis of European IPOs reveals that their mandates and priorities typically reflect the particular articulation of interests of development cooperation and business associations in each country. The paper concludes by presenting policy recommendations for Austria.
Keywords: 330; Import Promotion; Export Promotion; Structural Transformation; Global Value Chains; Import Information Hub Austria